2015
DOI: 10.1039/c5cp02191j
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio modelling of the anomeric and exo anomeric effects in 2-methoxytetrahydropyran and 2-methoxythiane corrected for intramolecular BSSE

Abstract: Accurate ab initio calculations including basis set limit (BSL) extrapolations, removal of intramolecular basis set superposition error (BSSE), solvent effect corrections, and thermal effects have been carried out to compare the structure and the anomeric and exo-anomeric effect in 2-methoxytetrahydropyran and 2-methoxythiane. The effect of intramolecular BSSE on the energetics was outlined for the first time in these types of compounds. It was found that both title compounds show comparable behaviour with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…[19] The contribution of this factor towards the anomeric effect, compared with other interaction mechanisms, has been estimated by high-level ab initio calculations. [87] More generally, our NCI plots on the fragments and conformers, both clockwise and counterclockwise, of GL and GA, highlight the C-H⋯O interactions between axial ring protons and oxygen atoms, notably that of the anomeric OH group, and the way these respond to pyridine complexation demonstrates cooperativity between this intramolecular interaction and intermolecular hydrogen bonding. This is particularly obvious in the results for the clockwise conformer of α-GL (Table 6) where the differences between the free conformer or partial structures and their pyridine complexes are exactly what it expected for a cooperative interaction: higher C-H proton NMR shifts and O6-H 4ax interaction energies, shorter hydrogen bonds.…”
Section: C-h⋯o Hydrogen Bond Cooperativitymentioning
confidence: 62%
See 1 more Smart Citation
“…[19] The contribution of this factor towards the anomeric effect, compared with other interaction mechanisms, has been estimated by high-level ab initio calculations. [87] More generally, our NCI plots on the fragments and conformers, both clockwise and counterclockwise, of GL and GA, highlight the C-H⋯O interactions between axial ring protons and oxygen atoms, notably that of the anomeric OH group, and the way these respond to pyridine complexation demonstrates cooperativity between this intramolecular interaction and intermolecular hydrogen bonding. This is particularly obvious in the results for the clockwise conformer of α-GL (Table 6) where the differences between the free conformer or partial structures and their pyridine complexes are exactly what it expected for a cooperative interaction: higher C-H proton NMR shifts and O6-H 4ax interaction energies, shorter hydrogen bonds.…”
Section: C-h⋯o Hydrogen Bond Cooperativitymentioning
confidence: 62%
“…It is reported that C―H⋯O interactions stabilise the axial conformation in 2‐substituted oxanes and 1,3‐dioxanes . The contribution of this factor towards the anomeric effect, compared with other interaction mechanisms, has been estimated by high‐level ab initio calculations . More generally, our NCI plots on the fragments and conformers, both clockwise and counterclockwise, of GL and GA, highlight the C―H⋯O interactions between axial ring protons and oxygen atoms, notably that of the anomeric OH group, and the way these respond to pyridine complexation demonstrates cooperativity between this intramolecular interaction and intermolecular hydrogen bonding.…”
Section: Discussionmentioning
confidence: 99%
“…The answer could possibly be obtained by comparing a stabilization by the n O4 → σ* C1−O1 and n O1 → σ* C1−O4 hyperconjugations (exemplified in Figure 6). By analogy with the well described 64,69,70 anomeric effect in a pyranose ring chair, these hyperconjugations can be related to the endo and exo anomeric effects, respectively (Table S2, Figure S1). This NBO analysis reveals a comparable stabilization of 1fur-2 E-a-cc and 5fur-2 T 1 -a-c by the n O4 → σ* C1−O1 interaction, but that by the n O1 → σ* C1−O4 interaction is found to be significantly weaker in the latter structure (Figure S1).…”
Section: Chain Conformersmentioning
confidence: 77%
“…This NBO analysis reveals a comparable stabilization of 1fur-2 E-a-cc and 5fur-2 T 1 -a-c by the n O4 → σ* C1−O1 interaction, but that by the n O1 → σ* C1−O4 interaction is found to be significantly weaker in the latter structure (Figure S1). Structurally, the O1−H1 bond is oriented approximately gauche to the C1−O4 bond in the four (more stable) 1fur-2 E-a-cc, 2fur-2 T 1 -a-c, 3fur-E 4 -a-cc, and 4fur-O T 1 -a-cc structures with the H1−O1−C1−O4 DA of 51.4−66.6°, whereas this orientation is approximately trans in the (less stable) 5fur-2 T 1 -a-c structure with the DA of −172.7°, which suggests that the exo anomeric effect 69 influences the relative stability.…”
Section: Chain Conformersmentioning
confidence: 97%
“…Thereafter, the mechanism of the addition reaction could be well understood: the selectivity for the syn diastereomer in the electrophilic activation manifolds is attributed to the increase of electrostatic and polarization terms, while that for the anti diastereomer in the nucleophilic manifold is explained by the decrease of electrostatic term. Similarly, using the decomposition of the difference of interaction energy in different geometries, the physical origins of the single σ bond rotations, the isomerization energies for azoborine, the gauche effect and the anomeric and exo‐anomeric effect, have been revealed based on the GKS‐EDA and LMO‐EDA calculations.…”
Section: Applicationsmentioning
confidence: 99%